2015
DOI: 10.1111/jfs.12192
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Cronobacter on gluB Gene and Differentiation of Four Cronobacter Species by Polymerase Chain Reaction‐Restriction Fragment Length Polymorphism Typing

Abstract: Cronobacter species are foodborne pathogens associated with neonatal meningitis, sepsis and necrotizing enterocolitis through consumption of contaminated powdered milk. However, there are no specific targets used for differentiating Cronobacter species. The DNA-based assay and polyphasic analysis have facilitated the detection and typing of Cronobacter species in foodborne outbreaks. In this study, polymerase chain reaction (PCR) and dot hybridization for detecting Cronobacter spp. was developed targeting gluB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Researchers have tested the addition of antimicrobials to PIF to control Cronobacter spp., including lactoferrin, nisin [121] , vanillin [75] and polyphenol-rich cocoa powder [122] . These all had good inhibitory effect on Cronobacter spp., although the safety of such antimicrobials needs to be fully assessed prior to [92] gluB Genus Lehner et al [93] tRNA Glu Genus Hassan et al [94] 23S rDNA Genus Derzelle et al [95] 16S rDNA Genus Hassan et al [94] wehC, wehI Species Mullane et al [96] zpx Genus Jaradat et al [97] wzx Genus Jarvis et al [98] gyrB Genus Huang et al [99] grxB Genus Dong et al [100] ompA Genus Zimmermann et al [101] MMS Genus Tan et al [102] cgcA Species Hu et al [103] rpoB Genus Li et al [104] ITS Genus Liu et al [105] PapC Species Chen et al [106] gluB Species YE et al [107] being recommended or approved for industrial application. The CDC, WHO and the US Food and Drug Administration have all provided guidelines to avoid contamination and infection of Cronobacter spp.…”
Section: Control Of Cronobacter In Pifmentioning
confidence: 99%
“…Researchers have tested the addition of antimicrobials to PIF to control Cronobacter spp., including lactoferrin, nisin [121] , vanillin [75] and polyphenol-rich cocoa powder [122] . These all had good inhibitory effect on Cronobacter spp., although the safety of such antimicrobials needs to be fully assessed prior to [92] gluB Genus Lehner et al [93] tRNA Glu Genus Hassan et al [94] 23S rDNA Genus Derzelle et al [95] 16S rDNA Genus Hassan et al [94] wehC, wehI Species Mullane et al [96] zpx Genus Jaradat et al [97] wzx Genus Jarvis et al [98] gyrB Genus Huang et al [99] grxB Genus Dong et al [100] ompA Genus Zimmermann et al [101] MMS Genus Tan et al [102] cgcA Species Hu et al [103] rpoB Genus Li et al [104] ITS Genus Liu et al [105] PapC Species Chen et al [106] gluB Species YE et al [107] being recommended or approved for industrial application. The CDC, WHO and the US Food and Drug Administration have all provided guidelines to avoid contamination and infection of Cronobacter spp.…”
Section: Control Of Cronobacter In Pifmentioning
confidence: 99%
“…One of the molecular methods which is used to identify Cronobacteria species is analyzing 16S rRNA genomic sequences, this gene is not able to differentiate some species such as C. sakazakii and C. malanticus due to their genetic similarity (Kucerova et al, ; Ye, Ling, Han, Cao, & Wu, ). Also, it has been observed that 16S rRNA gene sequences among the C. sakazakii group strains have high degrees of similarity (reaching 97.8–99.7%) (Iversen et al, ).…”
Section: Introductionmentioning
confidence: 99%